PENERAPAN PRODUKSI BERSIH PADA INDUSTRI KELAPA SAWIT DI PT YZ (Jurnal Teknologi Industri Pertanian, 2022)
PT YZ is a palm oil industry that has a processing capacity of 60 tons of FFB/hour with its main products in the form of Palm Oil (CPO) and Kernel. The palm oil industry in addition to producing the main product in the form of CPO, also produces a large amount of waste. The waste consists of solid waste, liquid waste and gas waste. The purpose of this research is to identify the flow of materials, products, and non-products in the production process of the palm oil processing industry and waste treatment processes, identify cleaner production alternatives that can be applied to the palm oil industry and determine the priority scale of cleaner production opportunities in the palm oil processing industry. The methods used include literature study, observation, mass balance analysis, technical feasibility analysis, economics (B/C and PBP), environmental, and Exponential Comparison Method (MPE). PT YZ has handled it by reusing the waste formed as boiler fuel (solid waste) and land application (treated liquid waste), but there were still waste and loss problems. The strategy for implementing cleaner production that technically, economically and environmentally feasible were 1) Modification of the process by adding a reservoir for condensate water and oil, with  B/C value = 2.5 and PBP = 0.50 years, 2) Application of good housekeeping by reducing dirt on fruit with GMP (good manufacturing practice) training, with B/C value = 1.61 and PBP = 1.63 years, 3) Application of good housekeeping by controlling or supervising the use of water by adding a water meter in each unit of process and repair of leaking pipes, with B/C value = 2.16 and PBP = 4.31 years and 4) The application of good housekeeping by reducing oil spills in the digester by repairing leaks in the digester tank and pipe, with B/C value = 1.48 and PBP 6.30 years. Based on the score obtained, it shows that the implementation of good housekeeping by reducing oil spills in the digester is the main priority.Keyword: cleaner production; MPE; palm oil